Histopathological Studies of the Effects of Nauclea Latifolia Ethanolic Root Extracts in Rats - C, Udeh Sylvester M.; N, Ogugua V.; E, Yakubu O.; O, Onaga A.; S, Egba; E, Anaduaka; N, Nghotu E.; P, Ugwu O.; M, Ude C.; J, Iornenge T.; J, Danjuma (Kwaghe International Journal of Sciences and Technology, 2024)
Nauclea latifolia (Smith) (Family: Rubiaceae) also known as ‘Pin Cushion tree’ or ‘African Peach’ is a struggling shrub, native in tropical Africa and Asia where the use of folk medicine is preval_ent and the search for herbal cure is but common practise. Extraction of the root of Nauclea latifolia with ethanol yielded the ethanol extract. The acute toxicity study on the ethanol extract in mice established an intraperitoneal LD50 greater than 4000mg/kg. Thus, the ethanol extract could be generally regarded as safe.. The histopathological sections of the liver and kidney of rats treated with ethanol extract of Nauclea latifolia showed that the extract contained some histopatotoxic compounds which might be responsible for the hepatocellular necrosis, inflammation and circulatory disturbances compared to the untreated rats. The present study established that the continuous administration of the ethanol crude extract of Nauclea latifolia is lethal to the hepatocytes and kidneys.